Comparison of Effectiveness and Safety between High-Power Short-Duration Ablation and Conventional Ablation for Atrial Fibrillation: A Systematic Review and Meta-Analysis. (16th August 2022) - Jin, Shuyu; Fu, Lu; Jiang, Junrong; Ye, Xingdong; Liu, Huiyi; Chen, Yanlin; Pu, Sijia; Wu, Shulin; Xue, Yumei
Abstract : Aim . We aimed to evaluate the effectiveness and safety between high-power short-duration (HPSD) radiofrequency ablation (RFA) and conventional RFA in patients with atrial fibrillation (AF). Methods . Studies comparing HPSD and traditional applications in patients undergoing initial catheter ablation for atrial fibrillation from inception through December 2021 were searched on Pubmed, Medline, Cochrane, and Clinicaltrials.gov . Results . The meta-analysis included seventeen studies with a total of 4934 patients. HPSD group decreased procedure duration (mean difference (MD) −38.28 min, P < 0.001 ), RF duration (MD −20.51 min, P < 0.001 ), fluoroscopy duration (MD −5.19 min, P < 0.001 ), and acute pulmonary vein reconnection (Odds ratio (OR) 0.40, P < 0.001 ), while improving the freedom from atrial arrhythmia at one year (OR 1.48, 95% confidence interval (CI) 1.12–1.94, P = 0.005 ) and rates of first-pass isolation (OR 8.92, P = 0.001 ). Compared with the conventional group, freedom from atrial arrhythmia at one-year follow-up was higher in the HPSD group without the guidance of AI/LSI (OR 1.66, P = 0.01 ) and studies with a power setting of 40–50 W (OR 1.93, P = 0.002 ). Nevertheless, the two groups had similar effectiveness with a power setting of 50 W in the HPSD RFA (OR 1.10, P = 0.52 ). There was no difference in complications between the two groups (P = 0.71 ). Conclusion . HPSD RFA was associated with shorter procedure duration, higher freedom from atrial arrhythmia, and comparable safety compared to conventional RFA.